2020
DOI: 10.1111/jmft.12447
|View full text |Cite
|
Sign up to set email alerts
|

Christian Mainline Protestant Pastors’ Beliefs About the Practice of Conversion Therapy: Reflections for Family Therapists

Abstract: Efforts to change the sexual orientation of lesbian, gay, and bisexual (LGB) individuals to heterosexual are referred to as conversion therapy. Given the religious groundings that support the practice of conversion therapy, we sought to explore the beliefs of Christian religious leaders about this practice and what they want family therapists to know about the practice of conversion therapy. Twenty-one pastors from diverse Mainline Christian Protestant traditions were interviewed. Queer theory-informed themati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The harmful impact of religiousbased SOCE were mirrored in studies of ex-gay ministries run by Evangelical Christians (Flentje et al, 2013(Flentje et al, , 2014. It is important to note that religious support for SOCE is not unanimous, as a study of Mainline Christian Protestant pastors found these religious leaders viewed SOCE as an abomination and "misuse of religion" (McGeorge et al, 2021).…”
Section: Change Efforts In Religious and Family Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…The harmful impact of religiousbased SOCE were mirrored in studies of ex-gay ministries run by Evangelical Christians (Flentje et al, 2013(Flentje et al, , 2014. It is important to note that religious support for SOCE is not unanimous, as a study of Mainline Christian Protestant pastors found these religious leaders viewed SOCE as an abomination and "misuse of religion" (McGeorge et al, 2021).…”
Section: Change Efforts In Religious and Family Contextsmentioning
confidence: 99%
“…The existing research connects the practice of SOCE and GICE with religious institutions and clinicians (Burack, 2015; Flentje et al, 2013; Grace, 2008). Scholars argue that the majority of clinicians who practice SOCE and GICE are affiliated with a religious tradition that supports such practices (Dehlin et al, 2015; McGeorge et al, 2021). Most of the current research focuses on SOCE with racially homogenous White samples, which means little is known about the use of GICE with those with marginalized gender identities and how such experiences intersect with religion and minoritized racial identities.…”
Section: Introductionmentioning
confidence: 99%
“…Religious counselors should also address the religious beliefs and cisheterosexist assumptions underlying their spiritual guidance or clinical practice. Addressing such biases does not imply deconstructing their religious beliefs, but rather exploring how their faith can impact their clinical practice [ 29 , 30 ]. Moreover, as families play a key role in pressuring children into conversion practices, they need to be supported and counseled in the acceptance of their LGBTQIA+ children.…”
Section: Discussionmentioning
confidence: 99%
“…The interview questions were created based on a careful review of the existing scholarly literature and with the assistance of a Christian pastor who had expertise working with individuals with marginalized sexual orientations and gender identities. The questions were also shaped by a previous study that explored pastors' beliefs about sexual orientation change efforts (McGeorge et al, 2021a). Examples of the questions in the interview guide include: What are your beliefs about transgender, nonbinary, and genderqueer identities?…”
Section: Methodsmentioning
confidence: 99%